Residues in the Secular: Whale Bones and Other Theological Relics1. Issue 4 (December 2015) - Marovich, Beatrice
Abstract: This article develops the concept of the "theological relic": a facet of secular life and culture that maintains traces of (and so remains bound in some way to) its genealogy in the theological. The theological relic, then, is something that fails to be either robustly religious or properly secular. It is, instead, a product of the relations between these social spaces. The article illustrates this concept by examining a cultural history of the whale, highlighting this creature's complex bonds with the theological. The whale, in other words, is figured as a theological relic: a creature of the secular that remains shrouded enough by traces of the theological that these vestiges of divinity are implicated in the whale's powerful late‐twentieth‐century cultural reconfiguration.